2021
DOI: 10.13075/ijomeh.1896.01841
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors affecting the disease acceptance in the group of women with postmenopausal osteoporosis

Abstract: Objectives: Assessment of the disease acceptance level in women with osteoporosis depending on selected sociodemographic factors. Material and Methods: The study included a group of 198 women, aged M±SD 72.3±8.59 years, diagnosed with postmenopausal osteoporosis and treated in 2 Osteoporosis Treatment Centres in Łódź. A questionnaire survey and Acceptance of Illness Scale (AIS) were applied in the study. Based on the questionnaire, the authors collected sociodemographic data (including age, marital status, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…They faced more barriers to implementing healthy practices and had less motivation for health [ 23 ]. A multicenter longitudinal study in Italy found a negative correlation between lower education level (45.8%) and body mass index(BMI) ( P = 0.013), smoking ( P < 0.001), and fractures ( P < 0.001) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They faced more barriers to implementing healthy practices and had less motivation for health [ 23 ]. A multicenter longitudinal study in Italy found a negative correlation between lower education level (45.8%) and body mass index(BMI) ( P = 0.013), smoking ( P < 0.001), and fractures ( P < 0.001) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WM method provided consistent effect estimates when at least 50% of the information in the analysis came from valid instruments. The heterogeneity was assessed using the Cochran’s Q test with the IVW method [ 18 ]. Heterogeneity was considered non-existent when the p -value of Cochran’s Q was > 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis is associated with elevated risk of fracture, which has become a growing major public health problem, with an impact on quality and quantity of life that crosses medical, social, and economic lines [ 2 ]. There was evidence revealing that osteoporosis influenced more than 200 million people all over the world [ 3 ]. The disease is more common in women than in men and especially prevalent among postmenopausal women who experience a decline in levels of endogenous estrogens [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Górczewska and Jakubowska-Pietkiewicz, 2022). Res has been used to treat postmenopausal osteoporosis patients as an estrogen replacement therapy(Liu et al, 2021).…”
mentioning
confidence: 99%